Redox electrode materials for supercapatteries - Yu, Linpo; Chen, George Z. (Elsevier, 2016)
Redox electrode materials, including transition metal oxides and electronically conducting polymers, are capable of faradaic charge transfer reactions, and play important roles in most electrochemical energy storage devices, such as supercapacitor, battery and supercapattery. Batteries are often based on redox materials with low power capability and safety concerns in some cases. Supercapacitors, particularly those based on redox inactive materials, e.g. activated carbon, can offer high power output, but have relatively low energy capacity. Combining the merits of supercapacitor and battery into a hybrid, the supercapattery can possess energy as much as the battery and output a power almost as high as the supercapacitor. Redox electrode materials are essential in the supercapattery design. However, it is hard to utilise these materials easily because of their intrinsic characteristics, such as the low conductivity of metal oxides and the poor mechanical strength of conducting polymers. This article offers a brief introduction of redox electrode materials, the basics of supercapattery and its relationship with pseudocapacitors, and reviews selectively some recent progresses in the relevant research and development.